Nash equilibrium selection using a hybrid two-player static game with trade-off ranking method - Muhammad Akram Ramadhan, Ibrahim; Nor Izzati, Jaini; Ku Muhammad Naim, Ku Khalif (PJSOR, 2024)
In the context of the game theory solution idea, the study seeks to suggest the ranking of an optimal solution when there are several Nash equilibria. The integration of the MCDM approach and game theory is a common strategy for addressing real-world challenges. This study introduces a novel hybrid method, combining a non-cooperative static game from game theory with the trade-off ranking (TOR) method from MCDM. The proposed hybrid method is used to rank multiple Nash equilibria concerning some criteria. The methodology for both static game and TOR method are explained in the paper. The game theory model used is a two-player non-constant-sum static game. The proposed methodology is tested using international cooperation in Iran. The result suggests the ranking of the combined strategies using the proposed method.